Pseudohypoaldosteronism Type 1—An Exercise in Clinical Deduction and Critical Management - Girish, Meenakshi; Pazare, Pradeep; Jaiswal, Archana; Banait, Yash; Kumar, Richa (Journal of Child Science, 2017)
Pseudohypoaldosteronism type 1 (PHA1) is a life-threatening disorder for two reasons, first because it causes severe hyperkalemia and second because the rarity of the disorder means that diagnosis is often delayed due to the lack of clinician familiarity with this condition. In this case report, we have described how even to an unsuspecting mind and eye, a systematic approach can lead to reversal of the severe hyperkalemia and arrive at the diagnosis of PHA1 as a cause of hyperkalemia. Long-term management can be successful only with dedicated care, and the prognosis is unfortunately worsened by the lack of availability of sodium-K resin in many countries, including India.
Keywords: pseudohypoaldosteronism type 1; hyperkalemia; acute management; long-term management; autosomal recessive